Mathematical Literacy through PBL-Team Teaching with Educaplay: A Case Study Based on Students’ Learning Styles - Rahmadani, Rhaesa Fadillah; Pusparani, Nilam; Noto, Muchamad Subali; Sundawan, Mohammad Dadan (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
This study aims to describe the mathematical literacy skills of junior high school students on the geometry of tubes and cones by applying the Problem-Based Learning (PBL) model with a team teaching strategy assisted by Educaplay digital media in terms of student learning styles. This study employed a descriptive qualitative approach with a case study design. The research subjects consisted of 30 eighth-grade students, with an in-depth analysis focused on three students, each representing a dominant learning style: visual, auditory, and kinesthetic. The research instruments included a learning style questionnaire, a mathematics literacy test based on local cultural contexts, and semi-structured interviews. The results indicated that visual learners tended to excel in interpreting visual contexts but struggled with abstract mathematical formulation. Auditory learners demonstrated understanding through verbal explanations but showed weaknesses in procedural aspects, while kinesthetic learners exhibited strong spatial reasoning through hands-on experiences. This study reveals that implementing the PBL model, integrated with team teaching strategies and the interactive media Educaplay, positively impacts the development of students’ mathematical literacy, taking into account differences in learning styles and their connection to local cultural contexts.